Heat Stress During the Transition Period is Associated with Impaired Production, Reproduction, and Survival in Dairy Cows - P. R. Menta; V. S. Machado; J. M. Piñeiro; W. W. Thatcher; J. E. P. Santos; A. Vieira-Neto (Kansas Agricultural Experiment Station Research Reports, 2022)
The objectives of this retrospective cohort study were to determine the association of heat stress exposure during the transition period with production, health, reproduction, and survival during the first 90 days postpartum in dairy cows. A total of 5,722 Holstein cows (2,324 heifers and 3,397 cows) were categorized into environmental condition (EC) groups based on average temperature humidity index (THI) exposure as thermoneutral (TN) or heat stress (HS) during the pre (Pre) and early postpartum (Post) periods into TN-TN, TN-HS, HS-TN, and HS-HS. In heifers, exposure to HS during the Pre, Post, or Pre and Post was associated with a 3.7-lb/d reduction in milk yield compared with TN-TN. Postpartum HS was associated with increases of 4.4-percentage points in incidence of retained placenta, 18.1-percentage points in incidence of metritis, and 2.0-percentage points in incidence of mastitis, and a reduction in 5.3-percentage points in pregnancy at first AI, and an increase in 4.5-percentage points in pregnancy loss compared with Post TN. In cows, exposure to HS during the Pre, Post, or Pre and Post was associated with a 5.3-lb/d reduction in milk yield when compared with TN-TN. Post HS was associated with an increased incidence of retained placenta of 5.8-percentage points within Pre HS cows, whereas no difference was found within Pre TN cows. Metritis was increased by 6.3-percentage points in Post HS cows. For pregnancy per AI, Post HS was associated with reduced pregnancy of 10.6-percentage points within Pre TN cows, whereas no difference was found within Pre HS cows. Removal from the herd increased in cows exposed to HS during the Pre or Post, or Pre and Post. These data suggest that early postpartum HS is associated with performance losses to a greater extent than prepartum HS and that heifers and cows are vulnerable to losses associated with exposure to HS during the transition period.
Keywords: transition period; heat stress; performance